`Acting under Chapter 7': rhetorical entrapment, rhetorical hollowing, and the authorization of force in the UN security council, 1995–2017 - Johannes Scherzinger (International Relations, 2022)
After more than 250.167emyears of scholarship, the deliberative turn in international relations (IR) theory is ready to be revisited with a fresh perspective. Using new methods from automated text analyses, this explorative article investigates how rhetoric may bind action. It does so by building upon Schimmelfennig's original account of rhetorical entrapment. To begin, I theorize the opposite of entrapment, which I call rhetorical hollowing. Rhetorical hollowing describes a situation in which actors use normative rhetoric, but instead of advancing their interests, such rhetoric fails to increase their chances of obtaining the desired outcome because the normative force of their rhetoric has eroded over time. To provide plausibility to both entrapment and hollowing, I present two mechanisms by which language is connected with action in the United Nations Security Council. Finally, I run a series of time-series-cross-section models on selected dictionary terms conducive to entrapment or hollowing on all speeches and an original Security Council resolution corpus from 1995 to 2017. The research shows that while mentioning 'human rights' is consistently associated with increased odds of authorization of force; the word 'terrorism' is associated with a decrease of odds for intervention. This finding suggests that some terms may not only entrap or hollow but also normatively backfire.
Keywords: 300; authorization of force; deliberative turn; quantitative text analysis; rhetorical entrapment; rhetorical hollowing